Grazing management innovation to improve animal production and reduce GHG emissions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The concept was proved that bites of 20cm of kikuyo grass improved milk productivity and reduced CH4 emissions compared to other grass heights. The next step will be piloting in farmers' field with representation of other grass species used for milk production in Colombia.